Atenuação de nível sonoro mediante uso de painéis absorvedores: estudo de caso em ginásio poliesportivo escolar - Silva, Eduardo Henrique (2018)
Multisports gyms in Brazil are buildings with extensive plastic variety in their architecture, which can be considered in several cities as visual references and, due to their use not only restricted to sports, for receiving multiple activities such as cultural events and fairs, these places influences on soundscapes due to the sound impact they generate in their surroundings. Once these places allows people accumulation and also because they are not acoustically treated for different activities due to the predominant presence of building elements with low acoustic absorption on their internal surfaces and various openings, the noise generated is amplified and dissipated, causing discomfort in the surrounding area. This work is a case study that intends to investigate noise reduction by absorption through the use of absorber panels inside a school sports gym in Maceió city. The methodology was based on the investigation of sound reflections in the environment, observing the reverberation time and the internal and external Leq (equivalent noise level), using the basis of Statistical Acoustics and different methods of in situ measurements imported from international standards and comparison with computational simulation of Geometric Acoustics and urban sound mapping. Sound absorbing panels with fixed NRC of 74% were distributed on the internal surfaces (walls and ceiling) of the selected gym, where it was possible to analyze 20 arrangements, defined in a matrix for simulation aiming at the most efficient combination. Among all the arrangements, the one with the greatest global noise reduction capacity reached - 8.4dB. Therefore, the noise reduction technique by absorption proved to be able to decrease the level of noise generated by the sound reflections inside the gym, attenuating the escape of sound to the surrounding area through its openings and also allowing the adoption of constructive strategies that cater to naturally acclimatized environments.